Análisis exploratorio de enfermedades Rickettsiales transmitidas por garrapatas en perros de Ciudad Juárez, Chihuahua, México - Escárcega, Angélica (2018)
During the last decade in northern Mexico, the interest in the study of zoonotic diseases such as anaplasmosis and canine ehrlichiosis, which are transmitted by ticks to both dogs and humans, has increased.The objective of this research was to evaluate the presence of Ehrlichia spp. and A. phagocytophilum in dogs and ticks from Ciudad Juarez, Chihuahua. The Polymerase Chain Reaction (PCR) technique determined a prevalence of 40% and 66% for Ehrlichia spp. and 27% and 13% for A. phagocytophilum in blood samples taken from dogs and in pools of Rhipicephalus sanguineus respectively. There was co-infection of both pathogens in 23% of the dogs and in 11% of the tick pools. The maximum value of the infection rate was 267.10, considering both pathogens. Rh. sanguineus was classified as a temperate lineage according to the sequencing analysis. The results suggest that there is a widespread infestation of Rh. sanguineus in the dog’s population. The pathogens associated with this tick species are circulating with a prevalence that goes from moderate to high, putting inhabitants of this border city at potential risk.